Synthesis of LaF3 inorganic nanoparticles: Er3+, Yb3+ by the coprecipitation method and characterization by optical spectroscopy and electron microscopy. (December 2018) - Luis Acosta, A; Puga, Rubén; Loro, Hector; Gómez, Karla Santacruz; Hernández, José Manuel; Acosta, Dwight
Abstract: It has been possible to synthesize LaF3 : Er 3+, Yb 3+ nanoparticles, which are light emitters by upconversion, using the co-precipitation method followed by a thermal treatment at temperatures of 400°C, 500°C and 600°C. In these nanoparticles, luminescence is attributed to upconversion process, where green and red radiative transitions emissions are observed under NIR irradiation of 980nm. The upconversion results reveals the emission dependence with Er 3+ and Yb 3+ concentrations in the synthesis of these nanoparticles, as well as their dependence on temperature as a result of the applied thermal treatment, being in all cases the most intense at 525nm, 546nm and 668nm. By means of diffuse reflectance spectra, the absorption bands of Er 3+ ions were obtained. On the other hand photoluminescence measurements were made for the identification of emission bands in Er 3+, in the visible range. Furthermore, data and additional information about crystalline nature of the material were obtained using the electron microscopy technique, in order to confirm the presence of LaF3, the obtained samples showed a good correspondence with the hexagonal phase. Thus, from the electron microscopy and optical spectroscopy results, it was verified that temperature increment in the thermal treatment of the nanoparticles, significantly influenced their morphology and luminescent intensity.